(untitled) (Nepalese Veterinary Journal, 2018)
In this study, we utilized a catch-vaccinate-release approach for dogs in a canine rabies vaccination program in Kotagiri municipality, India. Following vaccination, surveys on dog population and their vaccination status was undertaken. A bespoke smartphone ‘Mission Rabies’ application was developed to facilitate data entry and team management. This global positioning system (GPS) enabled application captured the location of all vaccinated dogs and dogs sighted on post-vaccination surveys. In areas where coverage was below 70%, catching teams were re-deployed to vaccinate additional dogs followed by repeat survey. Out of 248 dogs captured, only 210 dogs were vaccinated because of the previous vaccination history within a year, and refusal of owner due to their misconceptions. In survey, 147 dogs were sighted of which 77 were seen marked with paints indicating a vaccination coverage of 52.4%. The total estimated dog population was found to be 475. Our study demonstrated that mobile technology enabled efficient team management and real-time data entry and analysis. The vaccination approach outlined in this study can serve as a guideline for rapid vaccination of large numbers of dogs with a high coverage rate in free roaming dog populations in India in the future.